The Modern War Veteran: Identifying Needs, Problems and Risky Factors - Marcela Trávníčková; Jitka Laštovková; Benjamin Petruželka; Miroslav Barták (Vojenské rozhledy)
This article examines the needs and problems of the modern war veterans and identifies factors that may contribute to making them a high-risk group. It uses data from two questionnaire surveys. The respondents were war veterans leaving active service and war veterans who left active service less than ten years ago. The analysis shows that participation in the mission has a negative impact mainly on the family and relationships, and that the most common problems on leaving active service are related to finances and finding a new job. Services related to the new job are seen by respondents as the most beneficial. Further, few factors have been identified that may contribute to a high-risky group: less than nineteen years of service, age under forty, having health restrictions due to active service and leaving service as a decision of the employer.